2021
DOI: 10.3390/ijms22115645
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Na+ Modulates Pacemaking Activity in Murine Sinoatrial Node Myocytes: An In Silico Analysis

Abstract: Background: The mechanisms underlying dysfunction in the sinoatrial node (SAN), the heart’s primary pacemaker, are incompletely understood. Electrical and Ca2+-handling remodeling have been implicated in SAN dysfunction associated with heart failure, aging, and diabetes. Cardiomyocyte [Na+]i is also elevated in these diseases, where it contributes to arrhythmogenesis. Here, we sought to investigate the largely unexplored role of Na+ homeostasis in SAN pacemaking and test whether [Na+]i dysregulation may contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 77 publications
0
11
0
Order By: Relevance
“…We have previously demonstrated that even a small increase in [Na + ] i in response to Na + /K + pump inhibition by the digitalis glycoside (digoxigenin) perturbs SANC automaticity via impacting numerous coupled-clock mechanisms by producing changes in Na + and Ca 2+ electrochemical gradients [44]. A subsequent numerical modeling study [45] validated these experimental results. Additionally, like the modulation of SERCA2A Ca 2+ pumping by phosphorylation of PLB that modulates SERCA2A Ca 2+ pumping, phosphorylation of phospholemman modulates Na + /K + pump activity [46,47].…”
Section: Phosphatase Regulation Of Membrane Clock Proteinsmentioning
confidence: 71%
“…We have previously demonstrated that even a small increase in [Na + ] i in response to Na + /K + pump inhibition by the digitalis glycoside (digoxigenin) perturbs SANC automaticity via impacting numerous coupled-clock mechanisms by producing changes in Na + and Ca 2+ electrochemical gradients [44]. A subsequent numerical modeling study [45] validated these experimental results. Additionally, like the modulation of SERCA2A Ca 2+ pumping by phosphorylation of PLB that modulates SERCA2A Ca 2+ pumping, phosphorylation of phospholemman modulates Na + /K + pump activity [46,47].…”
Section: Phosphatase Regulation Of Membrane Clock Proteinsmentioning
confidence: 71%
“…From preclinical studies, it emerged that SSS pathomechanism(s) might be more complex than a deficit of a single channel or protein. The feedback between Ca 2+ handling and membrane potential clock might result also as altered, as shown in vivo by Torrente et al in an NCX −/− mouse model and confirmed in silico by Morotti et al simulating pathological modifications of intracellular Na + [170,171].…”
Section: Sss Due To Genetic Mutationsmentioning
confidence: 72%
“…To determine the potential cellular/ionic mechanisms underlying the observed SSS phenotype in the Dnajb6 +/- mice , we utilized a population-based computational modeling approach. We used our previously published model of the mouse SAN myocyte to generate a population of 10,000 model variants by randomly varying selected model parameters ( Figure 6A and B ; Morotti et al, 2021 ). In each variant, we simulated both sympathetic and parasympathetic stimulations and recorded baseline heart rate and heart rate responses to autonomic stimuli.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the cellular mechanisms underlying the SSS phenotype, we used our model of the mouse SAN myocyte, Morotti et al, 2021 based on the original model, Kharche et al, 2011 and including the formulation of the acetylcholine-activated K + current developed by Arbel-Ganon et al to simulate carbachol administration Arbel-Ganon et al, 2020 . Functional effects of isoproterenol administration on ion channels and transporters (listed in Supplementary file 6 ) were simulated as in the parent model, Kharche et al, 2011 wherein properties of isoproterenol-dependent modulation of voltage-gated Ca 2+ currents and funny current I f were updated to reflect experimental observations in mice Larson et al, 2013 ; Peters et al, 2021 .…”
Section: Methodsmentioning
confidence: 99%